PENAFSIRAN KESALEHAN AHLULBAIT DALAM KITAB AL-AMTHĀL FĪ TAFSĪR KITĀB AL-MUNAZZAL: STUDI Q.S Al-Insān [76]: 5-10 - Fatimah Isyti Karimah; Nurul Khair (Tanzil: Jurnal Studi Al-Quran, 2021)
This article is a literature review of the Al-Amthāl fī Tafsīr Kitāb al-Munazzal about piety of Ahlulbait by analyzing Q.S Al-Insān verses 5-10. The purpose of the analysis of Ahlulbait's piety in Q.S Al-Insān verses 5-10 is to explain the characteristics of a representative figure after the Prophet Muhammad that can eliminate the notion that there is a dichotomy between individual piety and social piety. This article will talk about the meaning of Ahlulbait's piety to explain the characteristics of al-Abrār which are described in Q.S Al-Insān verses 5-10. By using the descriptive historical method, the conclusion is that the piety of Ahlulbait reflected in Q.S Al-Insān verses 5-10 produces the characteristics of al-Abrār, carrying out vows perfectly, fearing the Day of Judgment, ith'am activities carried out to all elements of society, sincere in doing everything, only hope for Allah's pleasure alone and fear Allah on the day of Judgment. These five characteristics are related to one another to form a complete piety of the figure of Ahlulbait.